CIVIL LIABILITY: AN ANALYSIS OF THE LIABILITY OF ACCOUNTING PROFESSIONALS IN THE FACE OF BOOKKEEPING ACTS AUTHENTICATED BY THE BOARD OF TRADE - Campos, Edmilson Soares; Mergulhão, Danilo Rafael da Silva; dos Santos, Tiago Mota; Campos, Marcos Vinícius Pontes da Silva (Seven Editora, 2024)
The present research aims to analyze the civil liability of the Accountant in relation to the acts of bookkeeping authenticated by the Board of Trade. It is important to understand the civil liability of the accountant, as a liberal professional, within the scope of his duties, which include the preparation of reports, accounting entries, articles of incorporation, trial balances and financial statements, which are, depending on the legal nature of the organization, authenticated by the Securities and Exchange Commission, Boards of Trade and Registry Offices. The methodology adopted is based on a basic and qualitative research approach, based on the Accountant's Code of Ethics and on bibliographic, legal and jurisprudential analysis. The analysis revealed that the civil liability of accountants is a complex and multifaceted topic, covering legal, ethical and practical aspects that must be strictly observed by accounting professionals to ensure the integrity and legality of accounting information. The accountant's civil liability is an extremely relevant area that requires a constant commitment to ethics, legislation and the quality of accounting information. Thus, it goes beyond the civil and criminal spheres, covering a broader and more collective view.DOI: https://doi.org/10.56238/sevened2024.037-161